Waste Management in Higher Education Institutions: A Bibliometric Analysis of Past and Future Research Trends - Diky Sendhika Ardiantama; Gusman Nawanir (Universitas KH. Abdul Chalim Mojokerto, 2025)
This article aims to provide a comprehensive overview of waste management in higher education institutions, highlighting past research trends and potential future directions of articles. This article uses a bibliometric approach using 559 journals obtained from the Web of Science. Utilizing two analyses as mapping, namely (co-citation analysis and co-word analysis) to explore the current knowledge structure and identify future research directions related to waste management. Current research trends on waste management focus on developing frameworks and strategic implementation by considering certain important factors and decision-making strategies. In the future, articles on waste management will focus more on the overall framework and strategies for efficiently implementing waste management in higher education institutions, along with how to anticipate obstacles in its implementation. This article provides practical and theoretical benefits for further researchers and decision makers on waste management by increasing understanding of implementing waste management in higher education institutions. This article produces findings that can be utilized by researchers and decision makers in higher education institutions in implementing effective and efficient waste management, as well as encouraging continuous improvement efforts in the campus environment.